1959
DOI: 10.3181/00379727-101-24885
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Bacteriophages from Mother to Foetus in the Rat.

Abstract: 207mor cells, it is speculated that immunization has a lethal rather than a static effect on transplanted tumors.Discussion. McKee et aZ.(3) were unable to induce immunity by treatment with Ehrlich's ascites cells that had been killed by desiccation, freezing and thawing, mechanical grinding, and supersonic waves. The possibility exists that the physical-chemical changes of tumor antigens induced by in vitro x-irradiation are extensive enough to make the antigens less homologous and more antigenic for the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…It was observed that injection into the uterine lumen resulted in phage presence in fetal body fluids. In case of intravenous administration, phages were detected in fetus only in individual cases [230]. Opposite results were also reported, where phage ϕX174 was shown to be present in fetal blood samples after intravenous inoculation of a mother [231].…”
Section: Bacteriophages In Female Reproductive System and Pregnancymentioning
confidence: 81%
See 1 more Smart Citation
“…It was observed that injection into the uterine lumen resulted in phage presence in fetal body fluids. In case of intravenous administration, phages were detected in fetus only in individual cases [230]. Opposite results were also reported, where phage ϕX174 was shown to be present in fetal blood samples after intravenous inoculation of a mother [231].…”
Section: Bacteriophages In Female Reproductive System and Pregnancymentioning
confidence: 81%
“…were reportedly found in the bloodstream of newborn guinea pigs and placental samples after subcutaneous or intraperitoneal inoculation of mothers [229]. The passage of coliphages and mycobacteriophages across the placental barrier using a rat model was studied [230]. Methods of phage administration included intravenous injection and direct administration to the uterus.…”
Section: Bacteriophages In Female Reproductive System and Pregnancymentioning
confidence: 99%
“… Physiological changes during pregnancy and their impact on drug pharmacokinetics and consideration of these factors in the application of antenatal phage therapy (Kulangara and Sellers, 1959 ; Taylor, 1961 ; Uhr et al, 1963 ; Parry et al, 1970 ; Davison and Dunlop, 1980 ; Rasmussen and Nielsen, 1988 ; Clark et al, 1989 ; Cappell and Garcia, 1998 ; Frederiksen, 2001 ; Dabrowska et al, 2005 ; Jonczyk et al, 2011 ; Pacheco et al, 2013 ; Costantine, 2014 ; Leung et al, 2016 ; Speck and Smithyman, 2016 ). This figure includes a licensed image obtained by the authors.…”
Section: Route Of Administration and Transfermentioning
confidence: 99%
“…When treating the mother and fetus, it is essential to have a thorough understanding of the placenta and the extent to which drug transfer occurs across this maternal/fetal barrier. Kulangara et al (Kulangara and Sellers, 1959 ) examined the passage of coliphage and mycobacteriophages across the placental barrier of rats. Passage was achieved after injection into the uterine lumen as confirmed by presence of phage in the fetal fluids, however, maternal IV injection saw phage rarely reach the embryo.…”
Section: Route Of Administration and Transfermentioning
confidence: 99%
“…On the other hand, a discussion of mother mouse-to-fetus mouse migration of the T7-related phage, T3, includes the comment [16], “That phage remained viable in the animal (spleen) to 23 h was interesting.” This comment raises the possibility that phage T3 has a relatively high persistence in blood and, therefore, some phages for pathogenic hosts have similar high persistence. But, thus far, a direct test has not been performed for persistence in murine blood of phage T3.…”
Section: Introductionmentioning
confidence: 99%